2023
DOI: 10.17559/tv-20220414105757
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Problem of Friction and Wear in Auxiliary Devices of Internal Combustion Engines on the Example of Reciprocating Air Compressor for Vehicles

Abstract: Using vehicles and other mobile systems to transport passengers and goods, approximately 25% of Europe's greenhouse gases are generated. At the same time, many research papers, published by researchers and students, promote the use of electric vehicles as zero-emission vehicles. Given that, more broadly, the emission of electric vehicles is higher, especially in countries where electricity is obtained by burning coal, the use of internal-combustion engines is still dominant. There are other reasons for using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The effect of phosphorus 0.2% and 1% in grey cast iron has been investigated. Results showed that it leads to the development of a phosphide network and strengthens the metal matrix (Milojević et al, 2023). The effect of varying percentages of phosphorus in grey cast iron matrix in dry sliding conditions has been observed.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The effect of phosphorus 0.2% and 1% in grey cast iron has been investigated. Results showed that it leads to the development of a phosphide network and strengthens the metal matrix (Milojević et al, 2023). The effect of varying percentages of phosphorus in grey cast iron matrix in dry sliding conditions has been observed.…”
Section: Introductionmentioning
confidence: 88%
“…AlSi10Mg was reinforced with cast iron. It has been concluded that friction coefficient values were a minimum of 0.231 for reinforced alloy AlSi10Mg in comparison to 0.350 for plain ALSi10Mg alloy (Milojević et al, 2023).…”
Section: Introductionmentioning
confidence: 97%
“…On the tribometer, tribometer ball-type contact was made on a plate made of a sample of the tested materials in sliding conditions with and without lubricating oil. The tribometer manufactured by CSM Instruments SA, Peuseux, Switzerland, inside the Center for Tribology, was used for testing (Figure 5) [39,40]. Tribological tests were carried out by applying an appropriate force normal to the area of the tested material in the form of a plate.…”
Section: Applied Materials and Tribometer: Tests Under Sliding Condit...mentioning
confidence: 99%
“…At the same time, the optimization of peripheral devices and equipment on the IC engines, such as reciprocating air compressors in brake systems and air conditioning systems of passenger compartments, can additionally influence the reduction in mechanical losses, i.e., fuel consumption and emissions [39,40].…”
Section: Introductionmentioning
confidence: 99%